Analisis Semiotika Charles Sanders Peirce pada Elemen Visual Poster Film Ganjil Genap - Fitriani, Dian; Nurhandayani, Eti Fitri; Analisa, Widya (Besaung : Jurnal Seni Desain dan Budaya, 2025)
Film posters serve as a medium of visual communication that functions not only as a promotional tool but also as a cultural text representing social realities and aesthetic values. The urgency of this research is the film poster of Ganjil Genap by Bene Dion Rajagukguk, which features visual elements. This phenomenon shows that film posters can be an important object of study to understand how visual elements construct meaning and communication messages. This study aims to analyze the visual elements in the Ganjil Genap film poster using Peirce’s semiotic approach. The research employs a qualitative method and is conducted through four stages of design review: description, formal analysis, interpretation, and evaluation. In the descriptive stage, all visual elements of the poster are described in detail, including illustration, color, typography, and layout. The formal analysis stage examines how these elements are technically arranged to create visual harmony that attracts audience attention. The interpretation stage applies Peirce’s triadic concept of signs icon, index, and symbol to identify explicit and implicit meanings contained within each visual element. The final evaluation stage synthesizes the overall meanings derived from interpretation and assesses the effectiveness of the poster in conveying its message. The findings indicate that the Ganjil Genap film poster functions not merely as a promotional medium but also as a form of social and emotional communication. Through its carefully designed visual symbols and communicative strategies, the poster becomes a meaningful medium of visual communication capable of engaging audiences on a deeper emotional and cultural level.